Peripheral Synucleinopathy in Early Parkinson's Disease: Submandibular Gland Needle Biopsy Findings. Issue 2 (22nd January 2016) - Adler, Charles H.; Dugger, Brittany N.; Hentz, Joseph G.; Hinni, Michael L.; Lott, David G.; Driver‐Dunckley, Erika; Mehta, Shyamal; Serrano, Geidy; Sue, Lucia I.; Duffy, Amy; Intorcia, Anthony; Filon, Jessica; et al.
ABSTRACT: Introduction: Finding a peripheral tissue biopsy site to diagnose early PD would be of value for clinical care, biomarker validation, and as research enrollment criteria. Whereas autopsy and advanced PD studies suggest that the submandibular gland is an important biopsy site, there are no studies in early PD. The aim of this study was to determine whether needle biopsy of the submandibular gland reveals Lewy type alpha‐synucleinopathy in early PD. Methods: Twenty‐five early PD (duration < 5 years) and 10 controls underwent transcutaneous needle core biopsies of the submandibular gland. Tissue was stained for phosphorylated alpha‐synuclein, reviewed blind to clinical diagnosis, and only nerve element staining was considered positive. Results: Mean (standard deviation) age was 69.5 (8.3) for the PD group, 64.8 (8.0) years for controls, and disease duration 2.6 (1.1) years. Six PD and 1 control subject had inadequate glandular tissue. Positive staining was found in 14 of 19 (74%) PD and 2 of 9 (22%) control subjects. PD‐positive and ‐negative cases did not differ clinically. Adverse events (mainly swelling and bruising) were common (77% of cases), but were minor and transient. Conclusions: Submandibular gland needle biopsies identified phosphorylated alpha‐synuclein staining in 74% of early PD subjects. False positives may be true false positives or may represent prodromal PD. If confirmed in larger studies with eventual autopsy confirmation, the potential value of submandibular gland biopsies for early PD may be to aid in clinical trial inclusion/exclusion and eventually serve as a gold standard for biomarker studies short of autopsy confirmation. © 2016 International Parkinson and Movement Disorder Society